2022
DOI: 10.1093/ofid/ofac098
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes and Recovery of Patients who Survived COVID-19: LUNG INJURY COVID-19 Study

Abstract: Introduction LUNG INJURY COVID-19 (clinicaltrials.gov NCT 21/399-E) is a registry-based prospective observational cohort study to evaluate long-term outcomes and recovery 12 months after SARS-CoV-2 infection according to severity. Results 305 COVID-19 survivors were included (moderate: 162, severe: 143). 12 months after SARS-CoV-2 infection, there was resolution of respiratory symptoms (37.9% in severe versus 27.3% in moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…We identified 4710 records through PubMed, EMBASE, and ScienceDirect database searches. A total of 51 articles (i.e., 33,573 patients) were selected for analysis based on the inclusion and exclusion criteria [ 6 , 15 , 16 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The study selection process was documented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified 4710 records through PubMed, EMBASE, and ScienceDirect database searches. A total of 51 articles (i.e., 33,573 patients) were selected for analysis based on the inclusion and exclusion criteria [ 6 , 15 , 16 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The study selection process was documented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found elevations of D-dimer in post-COVID-19 patients, typically in the 20% and 30% range, and average D-dimer elevations are typically under 500 ng/ mL at follow-up, although levels as high as 2350 ng/mL have been observed. [23][24][25][26][27] Convalescent D-dimers were significantly elevated in patients requiring hospital admission and older than 50 years. 23 The elevated D-dimer levels found in this study (1425 ± 928 ng/mL) are much higher than those typically observed at follow-up and is comparable to admission D-dimer levels (1241 ± 1209 ng/mL) in these patients.…”
Section: Discussionmentioning
confidence: 96%
“…Their identification and the volumetric quantification may allow an easier classification in terms of gravity, extent and progression of the disease. Moreover, this may provide a high-impact tool to enhance awareness of the severity of COVID-19 pneumonia [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%